Screening of Pap smear and Cellular Abnormalities frequency - Dr. Naska M. Haseeb (Genius Journals, 2022)
Cytological screening for cervix with Papanicolau (Pap) smears has been used since the last century in many regions of the world. Cervical smear can be consider as one of the important diagnostic roles for detection of cervical abnormality including inflammation, intraepithelial lesions and even malignancy. Nearly all cervical malignancy are coming following intraepithelial cellular abnormality. The aim of this study is to check the number of females doing Papanicolaou (Pap) smear screening and their proportion with the cellular abnormalities frequency. Objectives and Methods: The study used was retrospective applied on 206 females records from July 2020 to July 2021 in Azady teaching hospital in Kirkuk. I focused on many variables including patients age, menopausal status and either within reproductive age or not, and abnormal changes in the smear. After analyzing data I presented them mainly as percentages; to assess associations, and the chi-square test used.
Keywords: mainly; associations; Kirkuk; reproductive